A Rare Case from Eastern part of Nepal: Young Female with Right-Sided Bovine Aortic Arch with Coarctation of Aorta and Takayasu's Arteritis - Yadav, Samir Kumar; Bhattarai, Anil; Baral, Ravi; Khakural, Prabhat; Khadka, Bibek (Journal of Institute of Medicine Nepal, 2024)
‘Bovine’ a misnomer term refers to a group of congenital abnormalities of the aorta in which there is aberrant origin of the left common carotid artery. Takayasu's arteritis is a rare, chronic inflammatory disease affecting the walls of the aorta and its main branches leading to stenosis, occlusions, dilatation, and aneurysms of involved vessels. It is rare to find both in a single patient. We present a 20 year young Muslim female from eastern Nepal complaining of pain and weakness of all four limbs, with cold digits for 3 months.